JUMPA Vol.3 No.2 Juni 2016 DETERMINASI PENERAPAN SISTEM INFORMASI LAYANAN AKADEMIKBERBASIS WEB: DETERMINASI PENERAPAN SISTEM INFORMASI LAYANAN AKADEMIKBERBASIS WEB - Diah Ernawati Perbanas Institute (Jurnal Manajemen dan Perbankan (JUMPA), 2016)
This research aims to determine the level of user (students) acceptance to the system by using the approach to the Technology Acceptance Model combined with the Structural Equation Model. The method used is the method of causal variables to be studied. This method will describe what factors are affecting the acceptance of Academic Services Information Web-Based System and the causal relationship between these factors. Given this research can be known what factors affect the acceptance of Academic Services Information Web-Based System, such as a factor of Perceived Ease of Use, a factor of Perceieved Usefulness, a factor of Attitude Toward Using and a factor of Actual System Usage, as well as the causal relationship between these factors. Moreover, the author can provide information, advice and feedback to stakeholders to improve services and student satisfaction.